The Role of Islamic Education in Countering Radicalism and Extremism in Pakistan: A Systematic Literature Review - Muhammad Memon (PT. Berkah Smart Academica, 2026)
The phenomena of radicalism and extremism in Pakistan remain persistent national security challenges frequently associated with Islamic educational institutions. This study aims to comprehensively synthesize the role of Islamic education in countering extremist ideologies by mapping the evolution of curriculum and pedagogy over the last five years. The methodology employed is a Systematic Literature Review (SLR) adhering to the PRISMA protocol, involving the analysis of 45 reputable academic references (Scopus, Sinta, Garuda, and Dimensions) published between 2021 and 2025. The data indicates a significant shift from closed theological education toward a hybrid model through the Single National Curriculum (SNC) policy, which integrates science, digital literacy, and critical thinking. Research findings reveal that the internal reform of Madrasahs and the strategic role of teachers as agents of moderation have effectively reduced potential cognitive radicalism at the grassroots level. In conclusion, Islamic education in Pakistan has transformed into a proactive counter-radicalization instrument through the theological deconstruction of violent narratives and the economic empowerment of students. This study recommends the necessity of continuous synchronization between national security policies and soft-power-based educational reforms to ensure long-term stability in the region.